Optical, structural, and transport properties of InN, In[subscript]xGa[subscript]1-xN alloys grown by metalorganic chemical vapor deposition - Khan, Neelam (Kansas State University, 2009)
InGaN based, blue and green light emitting diodes (LEDs) have been successfully produced over the past decade. But the progress of these LEDs is often limited by the fundamental problems of InGaN such as differences in lattice constants, thermal expansion coefficients and physical properties between InN and GaN. This difficulty could be addressed by studying pure InN and In[subscript]xGa[subscript]1-xN alloys. In this context Ga-rich In[subscript]xGa[subscript]1-xN (x≤ 0.4) epilayers were grown by metal organic chemical vapor deposition (MOCVD). X-ray diffraction (XRD) measurements showed In[subscript]xGa[subscript]1-xN films with x= 0.37 had single phase. Phase separation occurred for x ~ 0.4. To understand the issue of phase separation in Ga-rich In[subscript]xGa[subscript]1-xN, studies on growth of pure InN and In-rich In[subscript]xGa[subscript]1-xN alloys were carried out. InN and In-rich In[subscript]xGa[subscript]1-xN (x~0.97- 0.40) epilayers were grown on AlN/Al[subscript]2O[subscript]3 templates. A Hall mobility of 1400 cm[superscript]2/Vs with a carrier concentration of 7x1018cm[superscript]-3 was observed for InN epilayers grown on AlN templates. Photoluminescence (PL)emission spectra revealed a band to band emission peak at ~0.75 eV for InN. This peak shifted to 1.15 eV when In content was varied from 1.0 to 0.63 in In-rich In[subscript]xGa[subscript]1-xN epilayers. After growth parameter optimization of In- rich In[subscript]xGa[subscript]1-xN alloys with (x= 0.97-0.40) were successfully grown without phase separation. Effects of Mg doping on the PL properties of InN epilayers grown on GaN/Al[subscript]2O[subscript]3 templates were investigated. An emission line at ~ 0.76 eV, which was absent in undoped InN epilayers and was about 60 meV below the band edge emission peak at ~ 0.82 eV, was observed to be the dominant emission in Mg-doped InN epilayers. PL peak position and the temperature dependent emission intensity corroborated each other and suggested that Mg acceptor level in InN is about 60 meV above the valance band maximum. Strain effects on the emission properties of InGaN/GaN multiple quantum wells (MQWs) were studied using a single blue LED wafer possessing a continuous variation in compressive strain. EL emission peak position of LEDs varies linearly with the biaxial strain; a coefficient of 19 meV/GPa, characterizes the relationship between the band gap energy and biaxial stress of In[subscript]0.2Ga[subscript]0.8N/GaN MQWs.
Keywords: Metalorganic chemical vapor deposition (MOCVD); Growth; InN; In-rich InGaN; Epilayers; Light emitting diodes; Physics, Condensed Matter (0611)